Fluvial and coastal landform changes in the Aceh River delta (northern Sumatra) during the century leading to the 2004 Indian Ocean tsunami. Issue 5 (7th March 2022) - Chapkanski, Stoil; Brocard, Gilles; Lavigne, Franck; Tricot, Camille; Meilianda, Ella; Ismail, Nazli; Majewski, Jedrzej; Goiran, Jean‐Philippe; Alfian, Dedy; Daly, Patrick; Horton, Benjamin; Switzer, Adam; et al.
Abstract: River deltas are strongly affected by demographic growth and by the intensification of land use. The migration of deltaic coastlines is often rapid, threatening urban settlements, coastal farming, and coastal biotopes. Some deltas benefit from centuries of monitoring, such that the evolution of their coastline is well documented. For most deltas, however, such long records do not exist. The study of their geomorphological evolution can benefit from overlapping maps drafted over time, combined with aerial photographs and satellite images, to track the evolution of fluvial and coastal landforms. Both fluvial and coastal landforms are sensitive to variations in water and sediment supply, such that covariations in the evolution of these landforms, or the lack thereof, provide clues on the contribution of water and sediment supply to delta evolution. We document the evolution of river channels and coastlines in the delta of the Aceh River in northwest Sumatra, by overlying maps, ortho‐rectified aerial photographs, and satellite images covering the past 130 years. We assess the accuracy of the overlays, and then use multivariate statistics to analyze the co‐evolution of fluvial and coastal landforms. We propose that a progressive decrease in sediment supply spurred river channel lengthening and narrowing, landward migration of the shoreline, and narrowing of beach ridges. The 2004 Indian Ocean tsunami generated an instantaneous retreat of the coastline that amounts to ∼53% of the coastal retreat from 1884 to 2019 ce . Post‐tsunami evolution is marked by an irreversible acceleration of previous trends. Beach ridges located up‐drift of rivers and tidal channel mouths are more sensitive to long‐term landward retreat and tsunamigenic erosion. Abstract : GIS and multivariate analyses reveal coeval fluvial‐coastal landform changes in the Aceh River delta during the century leading to the 2004 Indian Ocean tsunamin (IOT). Decrease in river‐born sediments led to subsequent retreat of the shoreline until the delta was hit by the 2004‐IOT. The tsunami generated coastal retrogradation that amounts to ∼ 53% of the overall coastal retreat from 1884 to 2019. Therefore, post‐tsunami evolution only stands out as an irreversible acceleration of previous trends, rather than unusual dynamics.